Atitudes infantis face aos cuidados de saúde e perceção de dor: papel mediador dos medos médicos - Fernandes, S. C.; Arriaga, P.; Esteves, F. (Ciência e Saúde Coletiva, 2014)
This study intends to contribute to a better understanding of children’s attitudes and opinions regarding health care, mainly in terms of medical procedures, institutions and the efficacy of health professionals. The sample included 381 children, recruited from different schools in Lisbon. The more negative attitudes were attributed to institutions, while positive attitudes were related to the efficacy of health professionals. Medical procedures were considered less painful compared to potential day-to-day accidents. Higher levels of pain were reported by children of the female sex and by children during the primary education phase. Medical fears mediated the relationship between the perception of pain and children’s attitudes with respect to health care. Higher levels of pain perception were seen to be related to more negative attitudes regarding health care. However, this relationship was diminished when children’s fears about medical issues were contemplated. In conclusion, a translated instrument to assess children’s attitudes regarding health care is needed, as it may even contribute to the development of intervention programs within the scope of the promotion of attitudes towards health care.